If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 2y) + -1(x + 3y) = 1 Remove parenthesis around (2x + 2y) 2x + 2y + -1(x + 3y) = 1 2x + 2y + (x * -1 + 3y * -1) = 1 2x + 2y + (-1x + -3y) = 1 Reorder the terms: 2x + -1x + 2y + -3y = 1 Combine like terms: 2x + -1x = 1x 1x + 2y + -3y = 1 Combine like terms: 2y + -3y = -1y 1x + -1y = 1 Solving 1x + -1y = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'y' to each side of the equation. 1x + -1y + y = 1 + y Combine like terms: -1y + y = 0 1x + 0 = 1 + y 1x = 1 + y Divide each side by '1'. x = 1 + y Simplifying x = 1 + y
| 2x^2-19=0 | | -(8X^3+2X^2-6)+(4X^3-2X+9)= | | 7x-5=6x+2 | | 4x^2-32x+63=0 | | 7(2x-2)=14 | | 1-11(b-6)=-b-23 | | 5d+6-3d=12 | | -2(r+6)=-8r-6 | | 5m+31=-51-9m | | 4+-u=14 | | w^2+3w-18=0 | | 7-x+3x-3-9x= | | 2(r+3)= | | 29y=4(7y-6) | | y-36=7y | | 56=t+7t | | 2y+9=44-3y | | 4(x+2)+18= | | 2x-5=3+4x | | 4x^2+7x-3=0 | | 8x+4y= | | 2x+3x=18+2 | | x^2-19x+16=0 | | -(3xy-8)+4(5xy+6)= | | 9x=3x+30 | | 40=3t-13t | | 12x-5x=35 | | 2c-4=5c+11 | | 5x-7=153 | | -4(x+7)-43=6-45 | | 2x-4=-16 | | 3(X-4)+5(X+2)= |